PERILAKU HERDING BERDASARKAN TIPE INVESTOR DALAM KEPEMILIKAN SAHAM Studi Kasus pada Saham LQ-45 Periode September 2014Agustus 2017 - Gregorius Dolok Ambarita; Theodorus Sutadi; Rubiyatno Rubiyatno (EXERO : Journal of Research in Business and Economics, 2018)
This research focused on the herding behavior based on the types of investors in the Indonesian capital market 2014-2017. This research used the method of Vector Autoregression (VAR). The research consist of investor shares volume by using a sample of companies which listed on the stock index LQ-45 month period September 2014 to August 2017. The results of VAR analysis shows that the impact of herding behavior that is significantly affected by a fellow investor. The results of the IRF show a response to the average shock occurred during the first month, variance decomposition results show the impact of the behavior of fellow investors responded only type of investor. While the results of Granger causality show that there is a causal relationship between the type investors is going in one direction. The results of the four analyzes can explain the existence of herding behavior in the Indonesian capital market, although the effect only on a fellow investor type.